2016
DOI: 10.1016/j.nucmedbio.2015.11.007
|View full text |Cite|
|
Sign up to set email alerts
|

The inextricable axis of targeted diagnostic imaging and therapy: An immunological natural history approach

Abstract: Summary In considering the challenges of approaches to clinical imaging, we are faced with choices that sometimes are impacted by rather dogmatic notions about what is a better or worse technology to achieve the most useful diagnostic image for the patient. For example, is PET or SPECT most useful in imaging any particular disease dissemination? The dictatorial approach would be to choose PET, all other matters being equal. But is such a totalitarian attitude toward imaging selection still valid? In the face o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 133 publications
2
9
0
Order By: Relevance
“…For example, MR plays an important role in the phagocytosis of a virulent but not an attenuated strain of Mycobacterium tuberculosis ( Schlesinger, 1993 ). Reagents that specifically target the CD206 macrophage MR in humans are being developed for diagnostic imaging and therapy to inhibit tumor progression ( Cope et al, 2016 ). The clinical relevance of our findings can be inferred from the fact that the LmSd strain was isolated from a patient with chronic lesions and persisting organisms even after treatment and despite a strong cell-mediated immune response to Leishmania antigens ( Neva et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MR plays an important role in the phagocytosis of a virulent but not an attenuated strain of Mycobacterium tuberculosis ( Schlesinger, 1993 ). Reagents that specifically target the CD206 macrophage MR in humans are being developed for diagnostic imaging and therapy to inhibit tumor progression ( Cope et al, 2016 ). The clinical relevance of our findings can be inferred from the fact that the LmSd strain was isolated from a patient with chronic lesions and persisting organisms even after treatment and despite a strong cell-mediated immune response to Leishmania antigens ( Neva et al, 1979 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even more important for the patient is that this study portends the application of γ-tilmanocept to RA staging as it relates to pathotypical histopathology for RA and drug specificity responsiveness of RA to the RA pathotype. [43][44][45][46][47][48][49] In recent patient evaluations, Lewis et al identified transcriptional subgroups in synovium linked to three distinct RA pathotypes: fibroblastic pauci-immune pathotype, macrophage-rich diffuse-myeloid pathotype, and a lympho-myeloid pathotype characterized by infiltration of lymphocytes and myeloid cells. 48,50 This is suggestive of divergent pathogenic pathways or activation disease states.…”
Section: Discussionmentioning
confidence: 99%
“…The cells of tumor and TME secrete CCL2 and macrophage colony-stimulating factor (M-CSF) (Qian et al, 2011) and attract a large number of inflammatory monocytes to tumor sites where they differentiate into TAMs due to secretion of IL4, IL10, and IL13 (Wang and Joyce, 2010;Chuang et al, 2016). TAMs can be identified by CD163, CD200R, CD204, CD206, and HLA-DR low expression (Yang et al, 2015;Cope et al, 2016;Kubota et al, 2017). The recruited macrophages represent a significant part of the TME and provide significant support to the tumor.…”
Section: Macrophagesmentioning
confidence: 99%